Measurement of PM2.5 and Water-Soluble Ions at Central Tokyo, Japan and Source Apportionment - Shiori Ota; Junya Hanasaki; Kazuhiro Toki; Takuto Horigome; Akihiro Takemasa; Yuri Ohkoshi; Nami Takahashi; Yoshika Sekine (The Global Environmental Engineers, 2015)
Air pollution by fine particulate matter, PM2.5 has been inviting considerable concerns in East Asia. This study then aimed to characterize PM2.5 and its water-soluble ions collected at Shibuya, central Tokyo, Japan from July 2013 to May 2015, in order to better understand the air pollution mechanism and potential sources of PM2.5 of the city. Analytical results showed the PM2.5 was a mixture of aggregates of formless particles and its concentration ranged from 5.4 to 39μg/m3, with a mean of 14 ± 6.7μg/m3 (n=46). SO42- and NH4+ were abundant in PM2.5 and their presence mostly determined the variation of PM2.5 level. High concentration episodes were found in the season when air masses came from Asian continent, and a long-range transport of urban aerosols and soil-derived particles was suggested by changes in the chemical compositions.